The Effect of Learning Cycle 7E Model Assisted by PhET Simulation on Collaboration Skills and Physics Learning Outcomes of Vocational Students - Ria Arista; Subiki Subiki; Maryani Maryani (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2025)
Low student collaboration skills are often found in learning activities at school. This will certainly impact the low level of student learning outcomes. This study aims to examine the effect of the Learning Cycle 7E model assisted by PhET Simulation on students' collaboration skills and physics learning outcomes. This research is a true experimental study using a posttest-only control group design. The population in this study was class X students of SMK Negeri 2 Jember, while the research sample was determined using the cluster random sampling technique. Data collection methods included observation, interviews, tests, and documentation. The data obtained were analyzed using a normality test, followed by statistical tests using the Independent Sample T-test for collaboration skills and the Mann Whitney U-Test for physics learning outcomes. The results showed that the analysis of collaboration skills data using the Independent Sample T-test obtained a Sig. (2-tailed) of 0.000 ≤ 0.05, indicating a significant difference between the experimental and control groups. Meanwhile, the analysis of physics learning outcomes using the Mann Whitney U-Test obtained a Sig. (2-tailed) of 0.000 ≤ 0.05, also indicating a significant difference. Therefore, it can be concluded that the application of the Learning Cycle 7E model assisted by PhET Simulation has a significant positive effect on improving students' collaboration skills and physics learning outcomes.